Post-injury treatment with 7,8-dihydroxyflavone attenuates white matter pathology in aged mice following focal traumatic brain injury - Georgios Michalettos; Fredrik Clausen; Elham Rostami; Niklas Marklund (Neurotherapeutics)
Traumatic brain injury (TBI) is a major cause of morbidity and mortality, not least in the elderly. The incidence of aged TBI patients has increased dramatically during the last decades. High age is a highly negative prognostic factor in TBI, and pharmacological treatment options are lacking. We used the controlled cortical impact (CCI) TBI model in 23-month-old male and female mice and analyzed the effect of post-injury treatment with 7,8 dihydroxyflavone (7,8-DHF), a brain-derived neurotrophic factor (BDNF)-mimetic compound, on white matter pathology. Following CCI or sham injury, mice received subcutaneous 7,8-DHF injections (5 ​mg/kg) 30 ​min post-injury and were sacrificed on 2, 7 or 14 days post-injury (dpi) for histological and immunofluorescence analyses. Histological assessment with Luxol Fast Blue (LFB)/Cresyl Violet stain showed that administration of 7,8-DHF resulted in preserved white matter tissue at 2 and 7 dpi with no difference in cortical tissue loss at all investigated time points. Treatment with 7,8-DHF led to reduced axonal swellings at 2 and 7 dpi, as visualized by SMI-31 (Neurofilament Heavy Chain) immunofluorescence, and reduced number of TUNEL (Terminal deoxynucleotidyl transferase dUTP nick end labelling)/CC1-positive mature oligodendrocytes at 2 dpi in the perilesional white matter. Post-injury proliferation of Platelet-derived Growth Factor Receptor (PDGFRα)-positive oligodendodrocyte progenitor cells was not altered by 7,8-DHF. Our results suggest that 7,8-DHF can attenuate white matter pathology by mitigating axonal injury and oligodendrocyte death in the aged mouse brain following TBI. These data argue that further exploration of 7,8-DHF towards clinical use is warranted.